Prevalence of Water Borne Diseases in Flood Affected Areas of District Khairpur Mirs, Pakistan - Sajid Ali, Marvi Metlo, Zuheeb Ahmed, Sabit Ali, Sagheer Ahmed, Nazmeen Zafar, Nabeela Latif, Nisha Jamal (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study to observe the impact of flood on the prevalence of water borne disease. Methodology: A cross sectional observational study was conducted from July 2022 to September 2022 in flood affected areas of district Khairpur Mirs, Pakistan. The study was conducted on 910 patients after taking informed consent. Results: In this study 61% patients were males, 36% were female whereas only 3% participants were transgender. Majority of the patients belongs to rural areas while few belong to urban areas. Majority of the patients were of 01 to 10 years of age while only 43 patients were of age from 71- 80 years. Disease wise 397 case were of malaria, 156 patients were of diarrhea, 75 patients were of dysentery, 66 cases were of cholera, 89 cases were of typhoid fever, 76 cases were of skin diseases, 51 cases were of hepatitis. By keeping in view policy makers can take serious steps to treat the residents of district as well as took preventive measure to rescue the residents of district Khairpur Mirs. Conclusion: This study concludes that due to flood water accumulation water borne diseases increased. Among whole diseases malaria was on top with 44%, diarrhea was on second number with 17% while typhoid was on third number with 10% cases Keywords: Prevalence, Water borne diseases, Flood, Malaria, Diarrhea, Dysentery, Cholera, Typhoid fever, Skin diseases, Hepatitis.